Ti-6al-4v alloy wire for high-strength high-fatigue spinal connecting rod and preparation method thereof

CN122913282APending Publication Date: 2026-10-16ZHONGKE RUIJIN (SHANDONG) TITANIUM TECH CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611343639.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种高强高疲劳脊柱连杆用Ti-6Al-4V合金丝材及其制备方法,以解决现有技术存在的脊柱植入连杆用 TC4 合金丝材难以实现强度、塑性与高周疲劳性能的同步突破的技术问题

Benefits of technology

(1)本发明采用特定温度的固溶-时效耦合热处理工艺,先在Tβ-(170~220)℃温度下进行固溶热处理,该温度选于α+β两相区温度的上部区间,在该温度下能够确保一部分初生α相在加热过程中不完全溶解,控制初生α相的体积分数维持在35%-45%的较优区间,过高或过低的初生α相含量均不利于疲劳裂纹萌生阻力的提升;随后在Tβ-(390~420)℃温度下进行时效热处理,在该温度下能够发生相变驱动过程,其主要作用是促使固溶处理后保留下来的亚稳定β相充分分解,析出极其细密且高度弥散分布的次生α相片层,使得Ti-6Al-4V合金丝材呈现出一种以近等轴化初生α相为基体、其间镶嵌着由纳米尺度次生α相片层与极薄β膜构成的“β转变结构”的复合体,在疲劳载荷下,等轴化的初生α相因其晶体学取向的随机性和较短的位错滑移自由程,能有效分散局部塑性应变,延缓疲劳滑移带的形成,而弥散分布的细片状次生α相与β相界面则构成了大量强大的“微观障碍物”网络,迫使萌生的微裂纹在扩展时频繁发生偏折、分叉甚至止裂,大幅消耗裂纹扩展驱动力。固溶热处理和时效热处理耦合,有效消除了原始组织中连续晶界α相带来的应力集中隐患,减少了疲劳裂纹萌生的核心位点,同时细化的晶粒与均匀分布的两相界面能够阻碍位错运动,提升合金的抗变形能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122913282A_ABST
    Figure CN122913282A_ABST
Patent Text Reader

Abstract

The application provides a Ti-6Al-4V alloy wire for high-strength and high-fatigue spinal connecting rods and a preparation method thereof, and belongs to the technical field of medical titanium alloy materials. The preparation method of the Ti-6Al-4V alloy wire comprises the following steps: (1) vacuum consumable melting of raw materials to obtain a cylindrical ingot; (2) removal of the oxide skin of the cylindrical ingot, and then the cylindrical ingot is subjected to open-die forging, one-time rough rolling and two-time continuous rolling to obtain a rod; (3) heat drawing and diameter reduction treatment of the rod to obtain a wire; (4) solid solution treatment of the wire, cooling, then aging treatment, then surface compressive stress treatment to obtain the Ti-6Al-4V alloy wire. Through the solid solution-aging coupling heat treatment process at a specific temperature and the concave-convex double-roller straightening process, the finished Ti-6Al-4V alloy wire realizes the synchronous breakthrough of high strength, high toughness and high fatigue resistance, and fully meets the fatigue service requirement of titanium alloy under high load working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical titanium alloy materials technology, and in particular to a high-strength, high-fatigue spinal linkage Ti-6Al-4V alloy wire and its preparation method. Background Technology

[0002] Ti-6Al-4V (TC4) alloy, as an α+β dual-phase titanium alloy, has become the core material for the wire of spinal implant linkage due to its excellent biocompatibility, specific strength and corrosion resistance. Its four-point bending high-cycle fatigue performance directly determines the service life and safety of the implant.

[0003] Currently, fatigue strengthening of titanium alloy wires mainly relies on two types of techniques: heat treatment microstructure control and surface modification. However, both of these techniques have significant technical bottlenecks. For heat treatment microstructure control, conventional solution aging processes cannot accurately lock the temperature window of the two-phase region, making it difficult to control the volume fraction of the primary α phase within the optimal range of 35%-45%. This can easily lead to problems such as excessive primary α phase causing stress concentration or insufficient strength due to low content. At the same time, the metastable β phase decomposition is insufficient, and the secondary α phase is coarse and unevenly distributed, failing to form an efficient crack propagation barrier. For surface modification, in the field of surface strengthening, traditional shot peening and rolling processes have the defects of shallow stress layer, uneven stress distribution, and easy deterioration of surface roughness. Conventional roller straightening only achieves geometric shaping of the wire and cannot directionally introduce stable residual compressive stress, nor can it form a synergistic strengthening mechanism between heat treatment microstructure and surface stress field.

[0004] Among the existing publicly available technologies, invention patent CN118543695A discloses a method for preparing TC4ELI titanium alloy wire with excellent high-frequency fatigue strength. This method only controls the microstructure through a single heat treatment, without combining it with surface stress strengthening, resulting in limited improvement in fatigue performance. Utility model patent CN216780153U discloses a sinusoidal straightening device for titanium alloy coiled wire. This device only corrects the straightness of the wire, without introducing residual compressive stress or a synergistic microstructure control design, and therefore cannot meet the stringent service requirement of ≥2.5 million fatigue cycles for spinal linkage wire under a high load of 430N.

[0005] In summary, existing technologies cannot simultaneously achieve breakthroughs in the strength, plasticity, and high-cycle fatigue properties of TC4 alloy wires. There is an urgent need to develop a preparation technology for Ti-6Al-4V alloy wires that achieves simultaneous breakthroughs in high strength, high toughness, and high fatigue strength through the synergistic effect of precise microstructure control and directional strengthening of surface stress fields. Summary of the Invention

[0006] The purpose of this invention is to provide a high-strength, high-fatigue spinal linkage Ti-6Al-4V alloy wire and its preparation method, so as to solve the technical problem that the existing technology of spinal implant linkage TC4 alloy wire is difficult to achieve simultaneous breakthroughs in strength, plasticity and high-cycle fatigue performance.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a method for preparing Ti-6Al-4V alloy wire for high-strength, high-fatigue spinal linkages is provided, comprising the following steps: (1) Vacuum self-consumption smelting of raw materials to obtain cylindrical ingots; (2) Remove the oxide scale from the cylindrical ingot, and then proceed with the initial forging, first-pass rough rolling and second-pass continuous rolling to obtain the bar stock; (3) The bar is subjected to hot drawing to reduce its diameter, thereby obtaining wire; (4) The wire is subjected to solution treatment, cooled, aged, and then subjected to surface compressive stress treatment to obtain Ti-6Al-4V alloy wire.

[0008] Preferably, in step (1), the chemical composition of the Ti-6Al-4V alloy wire, by weight percentage, is Al: 5.5-6.5%, V: 3.5-4.5%, O: ≤0.13%, Fe: ≤0.25%, C: ≤0.08%, N: ≤0.05%, H: ≤0.012%, with the balance being Ti.

[0009] Preferably, in step (1), the Ti-6Al-4V alloy wire uses grade 1 or higher sponge titanium, metallic Al, metallic Fe and TiO2 as raw materials.

[0010] Preferably, in step (1), the raw materials are subjected to three vacuum self-consumption smeltings using a vacuum self-consumption furnace.

[0011] Preferably, in step (2), the temperature of the billet forging is 1150℃ and the holding time is 2.5 to 3 hours; the temperature of the first rough rolling is 950℃ and the holding time is 1.5 to 2 hours; the temperature of the second continuous rolling is 900℃ and the holding time is 1 to 2 hours.

[0012] Preferably, in step (4), a stepped resistance furnace is used to perform solution treatment in the α+β two-phase region at a temperature of T. β - (170~220)℃, heat preservation time is 0.5~1.0h; after solution treatment, it is rapidly cooled by water cooling, with a cooling rate of 25~200℃ / s.

[0013] Preferably, in step (4), an aging treatment is performed using a concave-convex double-roller straightener at a temperature below the recrystallization temperature, where the temperature is T. β- (390~420)℃, heat preservation time is 2.5~4.0h.

[0014] Preferably, in step (4), the extrusion temperature for applying surface compressive stress treatment is 30 to 65°C, and the number of extrusions is 1 to 2.

[0015] It should be noted that a stepped resistance furnace is used to first heat the wire in the two-phase region at temperature T. β Solution treatment is performed at (170~220)℃. Holding the solution at this temperature for a certain duration promotes the complete dissolution of some of the original β phase, while retaining an appropriate amount of equiaxed α phase, thus preventing plastic degradation due to excessive β phase dissolution. Then, the solution is placed below the alloy recrystallization temperature (T). β Aging treatment at 390–420 °C drives the precipitation of secondary α phase in the supersaturated solid solution in a fine and dispersed form, resulting in an optimized microstructure of "matrix β phase + dispersed secondary α phase". The β phase provides toughness to the wire due to its good plasticity, while the dispersed secondary α phase significantly enhances the matrix strength through grain refinement and dispersion strengthening effects, maintaining the α phase volume ratio within a reasonable range to balance the synergistic relationship between strength and plasticity. This microstructure control mechanism effectively eliminates the stress concentration hazards caused by the continuous grain boundary α phase in the original microstructure, reduces the core sites for fatigue crack initiation, and simultaneously, the refined grains and uniformly distributed two-phase interfaces hinder dislocation movement, improving the alloy's resistance to deformation.

[0016] A concave-convex twin-roller straightener is used to apply surface compressive stress to the solution-treated and aged wire. The refined α / β phase grains after solution treatment and aging provide structural conditions for the stable storage of residual compressive stress, while the residual compressive stress further strengthens the bonding effect at the two-phase interface, inhibiting the propagation of microcracks caused by α-phase grain slip and β-phase deformation during fatigue. At the same time, the extrusion action of the concave-convex twin-roller causes controllable elastoplastic deformation of the wire surface, which not only promotes the significant refinement of the surface grains due to dislocation proliferation, entanglement and intersection, forming a dense fine-grained layer, but also forms a uniformly distributed residual compressive stress on the surface. The crack closure effect induced by the surface residual compressive stress can reduce the effective stress intensity factor amplitude at the crack tip during alternating load cycles. This stress state can effectively offset the alternating tensile stress component under fatigue load, reduce the driving force for crack initiation, and make the crack propagation path tortuous due to the obstruction of fine grains and the constraint of the stress field, significantly improving the crack propagation resistance.

[0017] The present invention also provides a high-strength, high-fatigue spinal connecting rod Ti-6Al-4V alloy wire prepared by any of the above-described preparation methods.

[0018] Preferably, the Ti-6Al-4V alloy wire has a tensile strength ≥1150MPa, an elongation ≥17.0%, and a four-point bending fatigue life ≥2.5 million cycles under a load of ≥430N.

[0019] This invention provides a high-strength, high-fatigue spinal linkage Ti-6Al-4V alloy wire and its preparation method. Compared with the prior art, this invention has the following advantages: (1) The present invention employs a solution-aging coupled heat treatment process at a specific temperature, first at T β Solution heat treatment is performed at a temperature of (170~220)℃, which is selected in the upper range of the α+β two-phase region. At this temperature, it can be ensured that some of the primary α phase does not completely dissolve during heating, and the volume fraction of the primary α phase is controlled within the optimal range of 35%-45%. Too high or too low primary α phase content is not conducive to improving the resistance to fatigue crack initiation; subsequently, at T β - Aging heat treatment at (390~420)℃ can cause a phase transformation driven process. Its main function is to promote the full decomposition of the metastable β phase retained after solution treatment, and precipitate extremely fine and highly dispersed secondary α phase lamellars. This makes the Ti-6Al-4V alloy wire exhibit a "β transformation structure" with a near-equiaxed primary α phase as the matrix and embedded with nanoscale secondary α phase lamellars and extremely thin β films. Under fatigue load, the equiaxed primary α phase can effectively disperse local plastic strain and delay the formation of fatigue slip bands due to its random crystallographic orientation and short dislocation slip path. Meanwhile, the dispersed fine lamellar secondary α phase and β phase interface form a large number of powerful "microscopic barrier" networks, which force the microcracks that have started to propagate to frequently deflect, bifurcate, or even stop cracking, greatly consuming the crack propagation driving force. The coupling of solution heat treatment and aging heat treatment effectively eliminates the stress concentration hazards caused by the continuous grain boundary α phase in the original microstructure, reduces the core sites for fatigue crack initiation, and at the same time, the refined grains and uniformly distributed two-phase interfaces can hinder dislocation movement and improve the alloy's resistance to deformation.

[0020] (2) This invention introduces surface compressive stress treatment after the solution-aging coupled heat treatment process. Unlike conventional surface strengthening techniques, it uses a concave-convex double-roller straightener as a means to introduce residual surface compressive stress. Under the line contact high pressure of the straightening rollers, the microstructure of the outermost layer of the filament will be further nanoscaled, forming an extremely thin "gradient nanoscale layer" with extremely high dislocation density. This hardened layer is an efficient barrier to the initiation of fatigue cracks. The residual compressive stress field introduced by the surface compressive stress treatment generates a "force-" relationship with the optimized microstructure obtained through the solution-aging coupled heat treatment process. The "organizational synergistic effect" is as follows: On the one hand, the high compressive stress on the surface directly offsets most of the tensile stress component in the external alternating load, which mechanically increases the threshold value for fatigue crack initiation on the surface. On the other hand, when the external load is extremely high and the crack attempts to initiate in the transition zone or matrix below the compressive stress field, the internal microstructure, which is precisely controlled and rich in equiaxed primary α phase and fine lamellar secondary α phase, can effectively hinder the accumulation of dislocations on the subsurface and the formation of micropores, suppress the initiation and early connection of "internal origin" fatigue cracks, and significantly improve the crack propagation resistance.

[0021] (3) This invention utilizes a solution treatment at a specific temperature (T) β - (170~220)℃) - Aging (T) β - (390~420)℃) coupled heat treatment process, combined with concave-convex double roller straightening process (30~65℃), works synergistically on the wire to achieve excellent straightness of the wire while introducing high residual compressive stress on the surface of the wire. It is designed synergistically from two fundamental levels: "quantitative control of internal phase structure" and "active construction of surface stress state". It forms a synergistic strengthening mechanism of precise control of heat treatment structure and directional strengthening of surface stress field. The tensile strength of the finished Ti-6Al-4V alloy wire is ≥1150MPa, the elongation is ≥17.0%, and the four-point bending fatigue life of Ti-6Al-4V alloy wire is ≥2.5 million times under a load of ≥430N. It has achieved a simultaneous breakthrough in high strength, high toughness and high fatigue strength, and fully meets the fatigue resistance service requirements of titanium alloy under high load conditions. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1These are metallographic photographs of the Ti-6Al-4V alloy wires of Examples 1 to 3 of the present invention; wherein structure 1 is from Example 1, structure 2 is from Example 2, and structure 3 is from Example 3. Figure 2 The residual compressive stress distribution diagrams are shown for the Ti-6Al-4V alloy wires of Examples 1-3 of the present invention after surface compressive stress was introduced by the concave-convex double roller straightener; Figure 3 These are the cyclic fatigue curves of Ti-6Al-4V alloy wires under high load in Examples 1 to 3 of the present invention; wherein microstructure 1 is Example 1, microstructure 2 is Example 2, and microstructure 3 is Example 3. Detailed Implementation

[0024] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of this application and are not intended to limit the scope of this application. Unless otherwise specified, the methods used in this invention are conventional methods; the raw materials and apparatus used, unless otherwise specified, are conventional commercially available products.

[0025] To verify the reliability of the effectiveness of the present invention, the present invention will be described below with reference to Examples 1 to 3, and compared with Comparative Examples 1 to 5.

[0026] (I) Ti-6Al-4V alloy wire and its preparation method This invention provides a high-strength, high-fatigue spinal linkage Ti-6Al-4V alloy wire, which is composed of the components and their weight percentages of Examples 1-3 and Comparative Examples 1-5 in Table 1.

[0027] Table 1. Weight percentage of each component in the Ti-6Al-4V alloy wires of Examples 1-3 and Comparative Examples 1-5

[0028] This invention also provides a method for preparing the high-strength, high-fatigue spinal linkage Ti-6Al-4V alloy wire of Examples 1-3 and Comparative Examples 1-5 in Table 1, comprising the following steps: (1) Select grade 1 or higher sponge titanium, metallic Al, metallic Fe and TiO2 as raw materials, weigh and batch according to the weight percentage of each component in Table 1; then use a vacuum self-consuming furnace to perform three vacuum self-consuming meltings on the raw materials to obtain a cylindrical ingot with uniform composition, the ingot length is 1700mm and the cross-sectional diameter is 560mm. (2) Remove the oxide scale from the smelted cylindrical ingot, first perform forging at 1150℃, then perform rough rolling at 950℃, and then perform continuous rolling at 900℃ to obtain a bar with a diameter of 8.0mm. (3) The bar is subjected to hot drawing to reduce its diameter, and wire with diameter of Φ5.5-6.1mm is obtained; (4) First, use a stepped resistance furnace to heat the wire at a temperature T in the two-phase region. β Solution treatment was performed at (170~220)℃, followed by rapid cooling to room temperature via water cooling, and then the solution was placed below the recrystallization temperature T. β - The wire was aged at 390-420℃ and then subjected to surface compressive stress treatment by a concave-convex double roller straightener to obtain Ti-6Al-4V alloy wire with diameter 5.5-6.1mm.

[0029] The preparation processes of the Ti-6Al-4V alloy wires in Examples 1-3 and Comparative Examples 1-5 are shown in Table 2.

[0030] Table 2. Preparation process of Ti-6Al-4V alloy wires in Examples 1-3 and Comparative Examples 1-5

[0031] In the preparation methods of Examples 1-3 and Comparative Examples 1-5 above, in step (2), the billet is first forged at 1150°C, then roughed at 950°C in a single pass, and then rolled in a second pass at 900°C. As a preferred embodiment only, in actual production, the forging temperature is 1150°C, and the holding time is 2.5-3 hours; the roughing temperature is 950°C, and the holding time is 1.5-2 hours; the rolling temperature is 900°C, and the holding time is 1-2 hours. In actual production, adjustments can be made according to specific circumstances.

[0032] Metallographic analysis was performed on the Ti-6Al-4V alloy wires from Examples 1-3 to determine their phase transformation temperature T. β The temperature is 970–975℃.

[0033] (II) Testing of Ti-6Al-4V alloy wire To verify the effectiveness of the present invention, the Ti-6Al-4V alloy wires of Examples 1-3 and Comparative Examples 1-5 were tested below.

[0034] (1) Metallographic structure test Metallographic microscopy and scanning electron microscopy were used to test the microstructure of the Ti-6Al-4V alloy wires in Examples 1-3. The microstructure images are shown below. Figure 1 As shown.

[0035] Please see Figure 1 These are metallographic photographs of the Ti-6Al-4V alloy wires from Examples 1-3 of this invention. Figure 1 As can be seen from the examples, the Ti-6Al-4V alloy wires of Examples 1 to 3 exhibit a composite structure with a near-equiaxed primary α phase as the matrix and embedded with nanoscale secondary α phase sheets and an extremely thin β film, forming a "β transformation structure".

[0036] (2) Residual compressive stress test after surface compressive stress The residual compressive stress of the Ti-6Al-4V alloy wires in Examples 1-3 was tested using an X-ray stress analyzer and electropolishing equipment, in accordance with the standard GB / T 7704-2017 "Non-destructive Testing - X-ray Stress Measurement Method". The test conditions were as follows: at room temperature, the surface of the Ti-6Al-4V alloy wires in Examples 1-3 was peeled off layer by layer using electropolishing. The residual stress at each peeled layer was measured using X-ray diffraction until the stress decayed to zero, thereby obtaining the distribution curve of the residual compressive stress along the depth.

[0037] Please see Figure 2 This is a residual compressive stress distribution diagram of the Ti-6Al-4V alloy wires in Examples 1-3 of the present invention after surface compressive stress was introduced by a concave-convex double-roller straightener. From... Figure 2As can be seen, the residual compressive stress in Examples 1 to 3 all exhibit a typical gradient distribution characteristic of "high value at the surface and gradually decreasing to zero towards the interior". In Example 1, after two straightening treatments at 30°C, the maximum residual compressive stress at the surface is approximately -680 MPa, the total depth of the compressive stress-affected layer is approximately 120 μm, and the peak stress appears in the subsurface region about 30 μm from the surface. In Example 2, after two straightening treatments at 30°C, the maximum residual compressive stress at the surface is approximately -620 MPa, the depth of the compressive stress-affected layer is approximately 105 μm, and the peak stress appears about 25 μm from the surface. In Example 3, after one straightening treatment at 65°C, the maximum residual compressive stress at the surface is approximately -650 MPa, the depth of the compressive stress-affected layer is approximately 115 μm, and the peak stress appears about 28 μm from the surface. This gradient-distributed residual compressive stress field is a result of the high pressure exerted by the line contact of the concave-convex twin-roll straightener. During the straightening process, the surface of the Ti-6Al-4V alloy wire undergoes controllable elastoplastic deformation, which not only significantly refines the surface grains due to dislocation proliferation, entanglement, and intersection, forming a dense gradient nanoscale layer with a thickness of approximately 10–15 μm, but also creates a uniformly distributed residual compressive stress on the surface. This stress field generates a "force-structure" synergistic effect with the optimized microstructure obtained through a solution-aging coupled heat treatment process: On the one hand, the high compressive stress on the surface can directly offset the alternating tensile stress component under fatigue load, and significantly increase the threshold value for fatigue crack initiation on the surface through crack closure effect; on the other hand, the gradient attenuation of residual compressive stress towards the interior matches the refined α / β two-phase structure inside. When the external load is extremely high and the crack attempts to initiate in the transition zone below the compressive stress field, the uniformly distributed phase boundaries and grain boundaries inside can effectively hinder the accumulation of dislocations and the connection of microcracks, forcing the crack propagation path to deflect and bifurcate, and significantly increasing the crack propagation resistance.

[0038] (3) Room temperature tensile mechanical property test The room temperature tensile mechanical properties of the Ti-6Al-4V alloy wires from Examples 1-3 and Comparative Examples 1-5 were tested using a Zwick Z150 tensile testing machine. The tensile rate was 0.4 mm / min before yielding and 2.8 mm / min after yielding. Two parallel samples were taken from each group of specimens, and the average value was used as the room temperature tensile mechanical property of the specimen. The mechanical properties obtained from the test include tensile strength and elongation, and the results are shown in Table 3.

[0039] Table 3. Room temperature tensile mechanical properties and high load cyclic fatigue test results

[0040] As shown in Table 3, the Ti-6Al-4V alloy wires of Examples 1-3 have a tensile strength ≥1150MPa and an elongation ≥17.0%, which are superior to the Ti-6Al-4V alloy wires of Comparative Examples 1-5. This indicates that the Ti-6Al-4V alloy wires of Examples 1-3 have very high tensile strength and elongation, demonstrating excellent strength and toughness.

[0041] (4) High-load cyclic fatigue test High-frequency fatigue testing machines were used in conjunction with four-point bending fixtures to conduct high-load cyclic fatigue tests on Ti-6Al-4V alloy wires from Examples 1-3 and Comparative Examples 1-5, according to standard GB / T 3075-2021 "Methods for Controlling Axial Force in Fatigue Testing of Metallic Materials". The test conditions were as follows: using finished wires with their original surface intact, four-point bending cyclic loading was performed under a maximum alternating load ≥430N and a stress ratio R=0.1 to verify whether the wires could withstand 2.5 million cycles without fracture. The results are as follows... Figure 3 As shown in Table 3.

[0042] Please see Figure 3 The figures show the cyclic fatigue curves of the Ti-6Al-4V alloy wires in Examples 1-3 of this invention under high load. Figure 3 As can be seen, all three curves remain horizontal within the test range of 0 to 2.5 million cycles, and no load drop inflection point corresponding to fracture occurs. This indicates that the Ti-6Al-4V alloy wires of Examples 1 to 3 can stably withstand more than 2.5 million cycles of cyclic loading without fatigue failure under their respective set high loads.

[0043] As shown in Table 3, the Ti-6Al-4V alloy wires of Examples 1-3 exhibit a four-point bending fatigue life of ≥2.5 million cycles under a load of ≥430N. This indicates that the Ti-6Al-4V alloy wires of Examples 1-3 have high fatigue strength, fully meeting the fatigue resistance requirements of titanium alloys under high load conditions. In contrast, Comparative Example 1 fractured after 2.8 million cycles under a load of 361N, Comparative Example 2 fractured after 1.56 million cycles under a load of 328N, Comparative Example 3 experienced brittle fracture after only 123,000 cycles under a load of 412N, Comparative Example 4 fractured after 870,000 cycles under a load of 305N, and Comparative Example 5 fractured after 1.24 million cycles under a load of 322N. The load-bearing capacity and fatigue life of all comparative examples are significantly lower than those of Examples 1-3, directly demonstrating the breakthrough improvement of high-cycle fatigue performance achieved by the synergistic strengthening process of this invention.

[0044] Comparing Examples 1-3 with Comparative Example 1, it can be seen that although Comparative Example 1 used the same solution aging heat treatment process, it did not perform the twin-roll straightening process. Its surface lacked a compressive stress barrier, which resulted in the load-bearing capacity of the Ti-6Al-4V alloy wire decreasing to 361N and the elongation decreasing to 13.0%.

[0045] Comparing Examples 1-3 with Comparative Example 2, it can be seen that Comparative Example 2 uses ordinary stress-relief annealing instead of solution aging treatment, resulting in coarsened microstructure and no dispersed secondary α-phase reinforcement. The tensile strength and fatigue life (1.56 million cycles) of the Ti-6Al-4V alloy wire are significantly deteriorated.

[0046] Comparing Examples 1-3 with Comparative Example 3, it can be seen that the solution treatment temperature in Comparative Example 3 was too high (850°C), resulting in too few primary α phases and coarse β phases. At the same time, the high temperature of the twin-roll straightening process (85°C) caused the relaxation of residual compressive stress, which led to a sharp decrease in the fatigue life of the Ti-6Al-4V alloy wire to 123,000 cycles.

[0047] Comparing Examples 1-3 and Comparative Examples 4-5, it can be seen that Comparative Example 4 did not undergo solution treatment and directly entered the aging stage. Due to the lack of sufficient dissolution of alloying elements into the β phase and the formation of supersaturated solid solutions during the solution treatment process, the subsequent aging treatment could not drive the uniform precipitation of a large number of nanoscale secondary α phase lamellars. Only a small number of discontinuous precipitates could be formed at the original coarse β grain boundaries, which could not form an effective dispersion strengthening and grain refinement strengthening effect, resulting in a significant decrease in matrix strength. Its tensile strength was only 986 MPa, and it could only withstand 870,000 cycles under a low load of 305 N before fracturing. Comparative Example 5 did not undergo aging treatment. The metastable β phase formed by rapid cooling after solution treatment did not decompose. The microstructure lacked a secondary α phase interface that could hinder dislocation movement and crack propagation. At the same time, the volume fraction and morphology of the primary α phase were not optimized, and the synergistic relationship between strength and plasticity could not be balanced. Its tensile strength was 1012 MPa, and it fractured after 1.24 million cycles under a load of 322 N. The tensile strength and fatigue life of Comparative Examples 4-5 were significantly worse than those of Examples 1-3, which exhibited tensile strengths of 1183-1201 MPa and fatigue lives of ≥2.5 million cycles under a load of ≥430 N. This demonstrates that solution treatment and aging treatment are both indispensable; only through T... β - (170~220)℃ solution treatment and T β Only through the coupling effect of aging treatment at (390~420)℃ can the volume fraction of the primary α phase be precisely controlled within the optimal range of 35~45%, and the metastable β phase be fully decomposed to form a diffusely distributed secondary α phase, thus constructing an optimized dual-state structure of "near-equiaxed primary α phase + nano-secondary α sheets + ultra-thin β film", ultimately achieving a simultaneous improvement in tensile strength and fatigue life.

[0048] In summary, by Figures 1-3 As shown in Table 3, the Ti-6Al-4V alloy wires in Examples 1-3 underwent a coupled heat treatment process of solution treatment (750-800℃) and aging (550-580℃) at specific temperatures, combined with a concave-convex double-roller straightening process (30-65℃). The synergistic effect of these three processes resulted in an optimized bimodal microstructure of the Ti-6Al-4V alloy wires, based on a near-equiaxed primary α phase, with finely dispersed secondary α lamellae and β phases. This microstructure, on the one hand, enhances the tensile strength to 1183-1201 MPa through grain refinement and dispersion strengthening; on the other hand, the coordinated deformation capacity of the primary α phase and the plasticity of the β phase ensure that the elongation remains at 17.0-17.5%. More importantly, the gradient nano-layer and high residual compressive stress field introduced by the surface concave-convex double-roller straightening process produce a "force-structure" synergistic effect with the internal uniform and refined two-phase structure: on the one hand, the surface compressive stress directly offsets the tensile stress component in the external alternating load, inhibiting the initiation of fatigue cracks on the surface; on the other hand, the internally dispersed phase boundaries and grain boundaries hinder dislocation accumulation and microcrack connection; thus achieving an ultra-high fatigue life of ≥2.5 million cycles of four-point bending fatigue life under a load of ≥430N.

[0049] The Ti-6Al-4V alloy wire prepared by the raw materials and preparation method of this invention has a tensile strength ≥1150MPa and an elongation ≥17.0%. Under a load of ≥430N, the four-point bending fatigue life of the Ti-6Al-4V alloy wire is ≥2.5 million cycles. This invention achieves a simultaneous breakthrough in high strength, high toughness, and high fatigue resistance of Ti-6Al-4V alloy wire, fully meeting the fatigue resistance requirements of titanium alloys under high load conditions.

[0050] In summary, this invention provides a high-strength, high-fatigue spinal linkage Ti-6Al-4V alloy wire and its preparation method, which, compared with the prior art: (1) The present invention employs a solution-aging coupled heat treatment process at a specific temperature, first at T β Solution heat treatment is performed at a temperature of (170~220)℃, which is selected in the upper range of the α+β two-phase region. At this temperature, it can be ensured that some of the primary α phase does not completely dissolve during heating, and the volume fraction of the primary α phase is controlled within the optimal range of 35%-45%. Too high or too low primary α phase content is not conducive to improving the resistance to fatigue crack initiation; subsequently, at T β- Aging heat treatment at (390~420)℃ can cause a phase transformation driven process. Its main function is to promote the full decomposition of the metastable β phase retained after solution treatment, and precipitate extremely fine and highly dispersed secondary α phase lamellars. This makes the Ti-6Al-4V alloy wire exhibit a "β transformation structure" with a near-equiaxed primary α phase as the matrix and embedded with nanoscale secondary α phase lamellars and extremely thin β films. Under fatigue load, the equiaxed primary α phase can effectively disperse local plastic strain and delay the formation of fatigue slip bands due to its random crystallographic orientation and short dislocation slip path. Meanwhile, the dispersed fine lamellar secondary α phase and β phase interface form a large number of powerful "microscopic barrier" networks, which force the microcracks that have started to propagate to frequently deflect, bifurcate, or even stop cracking, greatly consuming the crack propagation driving force. The coupling of solution heat treatment and aging heat treatment effectively eliminates the stress concentration hazards caused by the continuous grain boundary α phase in the original microstructure, reduces the core sites for fatigue crack initiation, and at the same time, the refined grains and uniformly distributed two-phase interfaces can hinder dislocation movement and improve the alloy's resistance to deformation.

[0051] (2) This invention introduces surface compressive stress treatment after the solution-aging coupled heat treatment process. Unlike conventional surface strengthening techniques, it uses a concave-convex double-roller straightener as a means to introduce residual surface compressive stress. Under the line contact high pressure of the straightening rollers, the microstructure of the outermost layer of the filament will be further nanoscaled, forming an extremely thin "gradient nanoscale layer" with extremely high dislocation density. This hardened layer is an efficient barrier to the initiation of fatigue cracks. The residual compressive stress field introduced by the surface compressive stress treatment generates a "force-" relationship with the optimized microstructure obtained through the solution-aging coupled heat treatment process. The "organizational synergistic effect" is as follows: On the one hand, the high compressive stress on the surface directly offsets most of the tensile stress component in the external alternating load, which mechanically increases the threshold value for fatigue crack initiation on the surface. On the other hand, when the external load is extremely high and the crack attempts to initiate in the transition zone or matrix below the compressive stress field, the internal microstructure, which is precisely controlled and rich in equiaxed primary α phase and fine lamellar secondary α phase, can effectively hinder the accumulation of dislocations on the subsurface and the formation of micropores, suppress the initiation and early connection of "internal origin" fatigue cracks, and significantly improve the crack propagation resistance.

[0052] (3) This invention utilizes a solution treatment at a specific temperature (T) β - (170~220)℃) - Aging (T) β- (390~420)℃) coupled heat treatment process, combined with concave-convex double roller straightening process (30~65℃), works synergistically on the wire to achieve excellent straightness of the wire while introducing high residual compressive stress on the surface of the wire. It is designed synergistically from two fundamental levels: "quantitative control of internal phase structure" and "active construction of surface stress state". It forms a synergistic strengthening mechanism of precise control of heat treatment structure and directional strengthening of surface stress field. The tensile strength of the finished Ti-6Al-4V alloy wire is ≥1150MPa, the elongation is ≥17.0%, and the four-point bending fatigue life of Ti-6Al-4V alloy wire is ≥2.5 million times under a load of ≥430N. It has achieved a simultaneous breakthrough in high strength, high toughness and high fatigue strength, and fully meets the fatigue resistance service requirements of titanium alloy under high load conditions.

[0053] The above-described embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application, and should all be included within the protection scope of this application.

Claims

1. A method for preparing Ti-6Al-4V alloy wire for high-strength, high-fatigue spinal connecting rods, characterized in that, Includes the following steps: (1) Vacuum self-consumption smelting of raw materials to obtain cylindrical ingots; (2) Remove the oxide scale from the cylindrical ingot, and then proceed with the initial forging, first-pass rough rolling and second-pass continuous rolling to obtain the bar stock; (3) The bar is subjected to hot drawing to reduce its diameter, thereby obtaining wire; (4) The wire is subjected to solution treatment, cooled, aged, and then subjected to surface compressive stress treatment to obtain Ti-6Al-4V alloy wire.

2. The method for preparing the Ti-6Al-4V alloy wire for high-strength, high-fatigue spinal linkages according to claim 1, characterized in that, In step (1), the chemical composition of the Ti-6Al-4V alloy wire, by weight percentage, is Al: 5.5-6.5%, V: 3.5-4.5%, O: ≤0.13%, Fe: ≤0.25%, C: ≤0.08%, N: ≤0.05%, H: ≤0.012%, with the balance being Ti.

3. The method for preparing Ti-6Al-4V alloy wire for high-strength, high-fatigue spinal linkages according to claim 2, characterized in that, In step (1), the Ti-6Al-4V alloy wire uses grade 1 or higher sponge titanium, metallic Al, metallic Fe and TiO2 as raw materials.

4. The method for preparing the Ti-6Al-4V alloy wire for high-strength, high-fatigue spinal linkages according to claim 1, characterized in that, In step (1), the raw materials are subjected to three vacuum self-consumption smelting processes using a vacuum self-consumption furnace.

5. The method for preparing the Ti-6Al-4V alloy wire for high-strength, high-fatigue spinal linkages according to claim 1, characterized in that, In step (2), the temperature of the billet forging is 1150℃ and the holding time is 2.5 to 3 hours; the temperature of the first rough rolling is 950℃ and the holding time is 1.5 to 2 hours; the temperature of the second continuous rolling is 900℃ and the holding time is 1 to 2 hours.

6. The method for preparing the Ti-6Al-4V alloy wire for high-strength, high-fatigue spinal linkages according to claim 1, characterized in that, In step (4), a solution treatment is performed in the α+β two-phase region at a temperature of T. β - (170~220)℃, heat preservation time is 0.5~1.0h; after solution treatment, it is rapidly cooled by water cooling, with a cooling rate of 25~200℃ / s.

7. The method for preparing the Ti-6Al-4V alloy wire for high-strength, high-fatigue spinal linkage according to claim 6, characterized in that, In step (4), aging treatment is performed below the recrystallization temperature, at a temperature of T. β - (390~420)℃, heat preservation time is 2.5~4.0h.

8. The method for preparing the Ti-6Al-4V alloy wire for high-strength, high-fatigue spinal linkage according to claim 7, characterized in that, In step (4), the extrusion temperature for applying surface compressive stress treatment is 30-65℃, and the number of extrusions is 1-2.

9. A high-strength, high-fatigue spinal link Ti-6Al-4V alloy wire prepared by the preparation method according to any one of claims 1-8.

10. The Ti-6Al-4V alloy wire for high-strength, high-fatigue spinal linkages according to claim 9, characterized in that, The Ti-6Al-4V alloy wire has a tensile strength ≥1150MPa and an elongation ≥17.0%. Under a load of ≥430N, the Ti-6Al-4V alloy wire has a four-point bending fatigue life ≥2.5 million cycles.

Citation Information

Patent Citations

  • Titanium alloy disc round wire sine straightening device

    CN216780153U